Perilaku Seksual Pranikah Remaja Ditinjau dari Keterlibatan Orang Tua dan Tingkat Religiusitas - Andreas Yudha Fery Nugroho; Rini Eka Sari (Ilmu Psikologi Universitas Yudharta Pasuruan, 2022)
This study focuses on two factors that may influence the premarital sexual behavior of adolescents in Yogyakarta. The two factors are parental involvement and level of religiosity. Teenage premarital sexual behavior is one of the concerns, especially in Yogyakarta. The purpose of this study was to examine the relationship between the variables of adolescent premarital sexual behavior in terms of parental involvement and level of religiosity. The research method used is quantitative correlation with multiple regression techniques. Based on multiple linear regression testing in this study, the sig value was 0.082 or > 0.05. It is known that the significance value for the influence of parental involvement (X1) and the level of religiosity (X2) simultaneously on Y is 0.082 > 0.05 and F Count 2.559 > F Table 3.07, so it can be concluded that the hypothesis is rejected which means there is no significant effect. Simultaneous relationship between parental involvement and level of religiosity with adolescent premarital sexual behavior.